The Effect of Super Brain Yoga on Concentration, Memory, and Academic Progress in Nursing Students: A Quasi-Experimental Study - Pouran Varvani Farahani; Candan Ozturk; Abimbola Carew (International Journal of Community Based Nursing and Midwifery, 2024)
Background: During university life, students often face significant changes in relationships and academic pressures. Given the stressors faced by nursing students and the importance of their academic success, the study aimed to assess the impact of Super Brain Yoga on nursing students’ concentration, memory, and academic progress.Methods: This quasi-experimental study was conducted on 59 nursing students at Near East University in Cyprus from February to June 2023. The intervention group (N=29) performed Super Brain Yoga three times a week for two months, while the control group (N=30) continued the usual routines. Data were collected using the demographic questionnaire, Wechsler’s memory test, Concentration test, and the semester grade point average. Data analysis was performed using independent and paired t-test, chi-square, and ANCOVA using SPSS software version 26, with a significance level of P˂0.05.Results: The study revealed a significant difference in total memory scores (P<0.001) and its subscales including personal and public information (P<0.001), orientation (P<0.001), mental control (P<0.001), logical memory (P=0.002), repeating numbers (P<0.001), visual memory (P<0.001), and learning associations (P=0.003) between the experimental and control groups after the intervention. Findings revealed a significant difference between the two groups in the reaction time (P=0.003) and the error of the reverse counting (P=0.021) following the intervention. After the intervention, based on ANCOVA test with adjusting the baseline values, there was no statistically significant difference in the semester mean of Grade Point Average between the two groups (95% confidence interval, P=0.657)Conclusion: Super Brain Yoga is a non-invasive intervention that can improve memory, concentration, and cognitive abilities in nursing students.